Rare bird documentation form for Peregrine Falcon at the interchange of IA-130 and Interstate 80 in Davenport, 1985 - Blevins, Brian L.et al (1985)
Rare bird documentation form for a Peregrine Falcon at the interchange of IA-130 and Interstate 80 in Davenport in Scott County, IA on January 23, 1985. Epson - sheet feed